Trends and Rates of Stillbirths: An Observational Study in a Tertiary Level Hospital, Faridpur, Bangladesh - Fatema, Kaneez; Hossain, Hafsa; Tanjim, Taukir; Zesmin, Fahmida; Khanom, Nazmun Nahar; Shifa, Salma Afroz; Zeba, Dilruba (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Fetal death at any time during pregnancy is a very tragic situation for the parents and treating obstetricians. Pregnancy loss is a distressing problem and retention of dead fetus in utero has its own ill effects on physical, psychological, and social aspects. Mifepristone is commonly used for induction of labour when a fetus dies in the utero. This cross-sectional survey aimed to determine the incidence and trend of intrauterine fetal death and socio-demographic characteristics, maternal obstetric history, health seeking behavior among the women who experience a stillbirth delivery. It will also aim to evaluate the efficacy and safety of using Mifepristone in case of induction of labour. This study was done at the Obstetric & Gynecology department of Bangabandhu Sheikh Mujib Medical College and a total of 219 stillbirth deliveries were recorded out of 4275 total deliveries from January to December 2022, resulting in a stillbirth rate of 51 per thousand live births. The majority of stillbirths were preterm between 28-38 weeks, and more than half were delivered via normal vaginal deliveries. The study revealed poor distribution of prenatal care, with only 9.59% of mothers having had the recommended 4 ante natal care visits, while 29.22% were primiparous. The results underscore the need for effective prenatal care to reduce the incidence of stillbirth and highlight the importance of careful management of intrauterine fetal death cases to mitigate physical, psychological, and social effects. The findings of this study provide valuable information for clinicians, policy makers, and researchers working in the field of obstetrics and gynecology. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):38-43